Glas in beeld – beeld in glas. Verkondiging in fragment en fragmente van verkondiging ... - Kloppers, Elsabé (HTS teologiese studies, 2015)
Glass in the image – image in glass. Preaching in fragments and fragments of preaching . . . The view that the sermon is an ‘open work of art’, promoted the awareness that the ‘meaning’ of a sermon is not fixed, but that possibilities are presented for the listeners to ‘assign meaning’. ‘Assigning meaning’ does not mean something fully ad libitum: ‘meaning’ is formed within the guidelines of the text from which a sermon stems. Visual works of art could also be based on Biblical texts or stories, analysed and interpreted by the artist. The artist could mould the encounter with the Biblical text into various forms of art, proclaiming the gospel in ways similar to that of a spoken sermon: a work of art could present possibilities for assigning meaning related to faith. In this article the new stained glass windows, symbolically depicting the Liturgical Year, in a Dutch Reformed church in Pretoria, are discussed with a view to the possibilities they present to form part of experience-based religious education in ‘bringing home’ stories from the Bible and aspects of the Liturgical Year. Also asked is how they could function as visual ‘sermons’, speaking and communicating the ‘Word of God’ to the people inside the church, as well as to people on the outside.